Exploring the Potential Herbicidal Activity of Actinomycetes Isolated from Western Ghats Soil, India - C. V. Babu; B. N. Ramesh; P. Bhavani; B. S. Lalitha (Indian Journal of Microbiology, 2026)

Decoding nutrient dynamics in coastal aquifers: Machine learning insights into submarine groundwater discharge and seawater intrusion in south India - V. Gopalakrishnan; K. Srinivasamoorthy; A. Rajesh Kanna; C. Babu; K. Ramesh; D. Supriya Varshini; P. Muhammed Farsin; Aleena G. Raj (Chemosphere, 2025)

Genetic mapping of tolerance to iron deficiency chlorosis in peanut (Arachis hypogaea L.) - Ankur D. Tayade; Babu N. Motagi; Mangesh P. Jadhav; Anjum S. Nadaf; Rajshekar V. Koti; Sunil S. Gangurde; Vinay Sharma; Rajeev K. Varshney; Manish K. Pandey; Ramesh S. Bhat (Euphytica, 2022)

Hydrothermal activity in the basement granite associated with the unconformity-related uranium deposit in Chitrial area, Cuddapah Basin, India - Jugina Thomas; M S Pandian; Tresa Thomas; P K Thomas; S J Chavan; P V Ramesh Babu; H S Rajaraman (Journal of Earth System Science, 2021)

Amphibolites in the rare metal- and tin-bearing Bastar–Malkangiri pegmatite belt in Chhattisgarh and Odisha, India - P V Ramesh Babu; R Dhana Raju (Journal of Earth System Science, 2019)

Mineral chemistry of tourmaline from Mashak Pahar, South Purulia Shear Zone (SPSZ), eastern Indian Shield - SANTANU ACHARJEE; JYOTISANKAR RAY; PAYEL DEY; DEBAPRIYA BHATTACHARYYA; MOUSUMI BANERJEE; BASAB CHATTOPADHYAY; SHYAMAL SENGUPTA; A K BHATT; D CHOWDHURY; A K DWIVEDI; SANJOY MAHATO; ARKA RANJAN JANA; et al. (Journal of Earth System Science, 2016)

Synthesis, characterization and molecular docking studies of novel 2-amino 3-cyano pyrano[2,3H]chrysin derivatives as potential antimicrobial agents - P. Ramesh; Ch. Sanjeeva Reddy; K. Suresh Babu; P. Muralidhar Reddy; V. Srinivasa Rao; T. Parthasarathy (Medicinal Chemistry Research, 2015)

Ianthinite: A rare hydrous uranium oxide mineral from Akkavaram, Andhra Pradesh, India - YAMUNA SINGH; R VISWANATHAN; K K PARASHAR; S K SRIVASTAVA; P V RAMESH BABU; P S PARIHAR (Journal of Earth System Science, 2014)

Development and characterization of cell lines derived from rohu, Labeo rohita (Hamilton), and catla, Catla catla (Hamilton) - V P Ishaq Ahmed; V Chandra; R Sudhakaran; S Rajesh Kumar; M Sarathi; V Sarath Babu; B Ramesh; A S Sahul Hameed (Journal of Fish Diseases, 2009)
Two new cell lines, designated RE and CB, were derived from the eye of rohu, Labeo rohita , and the brain of catla, Catla catla , respectively. The cell lines were maintained in Leibovitz’s L‐15 supplemented with 20% foetal bovine serum. The RE cell line was sub‐cultured for more than 70 passages and the CB cell line for more than 35 passages. The RE cells are rounded and consist predominantly of epithelial cells. The CB cell line consists of predominantly fibroblastic‐like cells. Both cell lines are able to grow at temperatures between 25 and 32 °C with an optimum of 28 °C. The growth rate of the cells increased as the foetal bovine serum concentration increased from 2% to 20% at 28 °C, with optimum growth at concentrations of 15% or 20% foetal bovine serum. The cells were successfully cryopreserved and revived at different passage levels. The cell lines were not susceptible to four marine fish viruses. Extracellular products from Aeromonas sp . were toxic to the cell lines. When the cells were transfected with plasmid eukaryotic green fluorescent protein (pEGFP [Clontech, Carlsbad, CA, USA]) vector DNA, a significant fluorescent signal was observed suggesting that these cell lines could be a useful tool for transgenic and genetic manipulation studies. Polymerase chain reaction amplification of mitochondrial 12S rRNA from rohu and catla confirmed that the cell lines originated from these fish species. The cell lines were further characterized by immunocytochemistry using confocal laser scanning microscopy.